Customer value as the engine of brand image: Evidence from HR competence, service quality, CRM, and banking technology at BRI Depok - Basri, Hasan (Privietlab, 2025)
This study examines how internal capabilities and relationship processes—human resource competence, service quality, customer relationship management (CRM), and banking technology—shape customer value and, through it, brand image at PT Bank BRI (Persero) Tbk., Depok Branch. Using a cross-sectional survey of retail customers and Partial Least Squares Structural Equation Modeling (PLS-SEM), we validate reliable reflective measures for all constructs and test a mediation model positioning customer value as the central mechanism linking firm capabilities to brand outcomes. The structural results show that CRM is the strongest predictor of customer value (β ≈ 0.382), followed by human resource competence (β ≈ 0.266) and service quality (β ≈ 0.242); banking technology is positive but not significant once other drivers are controlled (β ≈ 0.095, n.s.). Customer value strongly influences brand image (β ≈ 0.740), explaining a substantial share of its variance (R² ≈ 0.547), while the four antecedents jointly explain most of the variance in customer value (R² ≈ 0.787). These findings indicate that brand building in banking is fundamentally a value-delivery challenge: day-to-day CRM discipline, service execution, and frontline competence translate into reputational gains more than technology per se—unless technology visibly improves the lived experience. Managerially, the priorities are to make CRM “felt,” coach people to remove customer effort, and keep SERVQUAL routines visible; technologically, target experience outcomes (e.g., resolution time, seamless handoffs) rather than features. Limitations and replication paths are discussed.